STIGMA DAN KRIMINALITAS : STUDI KASUS STIGMA DUSUN BEGAL DI BANGKALAN MADURA - Fitria Dayanti; Martinus Legowo (Universitas Pendidikan Nasional, 2021)
The existence of criminal acts of robbery in an area has a bad influence on the area. The criminal case of robbery that occurred in Candih Hamlet brought new problems to the good name and image of the Hamlet. Stigma and bad labeling began to emerge in the village. This study focuses on the forms of stigma received by the Candih Hamlet community, as well as the response from the community to the stigma given. This study uses a descriptive qualitative method with the research subjects of village elders and the indigenous people of Candih Hamlet. The theory used in this research is Erving Goffman's stigma theory. Data collection techniques were carried out by in-depth interviews, field observations, and documentation. The data analysis technique used is interactive analysis with steps of data reduction, data presentation, and drawing conclusions. The results of this study are the forms of stigma that are accepted by the people of Candih Hamlet. The existing stigma is verbal and non-verbal. Verbal stigma in the form of nicknames or labeling in the hamlet is the nickname